Pola Konsumsi Karbohidrat dan Status Gizi pada Siswa Kelas XI SMAN 1 Sampara - Rifa’atul Mahmudah; I Putu Sudayasa; Muhammdad Rustam; La Ode Alifariki (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2019)
Nutritional problems that are happening in Indonesia in this era of globalization are multiple nutrition problems, namely lack and excess nutrition. The results of the obesity examination in Southeast Sulawesi in 2016 showed that of 86,430 residents aged 15 years and over who were examined, 22,025 or 25.48% were obese. Lifestyle and diet are things that can affect the nutritional status of adolescents. As a result of the condition of malnutrition are disrupted child growth, lack production of energy, lack of endurance, disruption of intelligence and behavior. While the result of excess nutrition is the occurrence of obesity which can cause degenerative diseases and metabolic diseases. This study aims to determine the relationship of carbohydrates consumption patterns with nutritional status in eleventh grade students. This study was an observational analytic study with a cross sectional design. The population of this study were the eleventh grade students of SMAN 1 Sampara. The sample of this study were 121 peoples. The sampling technique has been using simple random sampling method. Data was taken using Food Frequency Questionnaire (FFQ), weight scale, and microtoice. Data analysis was using Spearman correlation test with p value <0.05 and correlation coefficient (r). The results of the analysis showed that there was no relationship of carbohydratesconsumption patterns (p = 0.215 and r = 0.113) with nutritional status status in eleventh grade students. The conclusion of this study is there is no relationship of carbohydrates consumption patterns with nutritional status status in eleventh grade students of SMAN 1 Sampara in Sampara District.